2014
DOI: 10.1038/cdd.2014.205
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of epithelial–mesenchymal transition and apoptotic pathways by miR-294/302 family synergistically blocks let-7-induced silencing of self-renewal in embryonic stem cells

Abstract: The embryonic stem cell (ESC)-enriched miR-294/302 family and the somatic cell-enriched let-7 family stabilizes the self-renewing and differentiated cell fates, respectively. The mechanisms underlying these processes remain unknown. Here we show that among many pathways regulated by miR-294/302, the combinatorial suppression of epithelial–mesenchymal transition (EMT) and apoptotic pathways is sufficient in maintaining the self-renewal of ESCs. The silencing of ESC self-renewal by let-7 was accompanied by the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 56 publications
6
32
0
1
Order By: Relevance
“…Consistent with cellular phenotypes, RT-qPCR analysis verified that mesenchymal marker Cdh2 and key transcription factors promoting epithelialto-mesenchymal transition (EMT) are upregulated in Mbnl1/2 overexpressing ESCs (Fig 6E). We and others have previously shown that miR-294 promotes ESC proliferation and G1/S transition, and inhibits apoptosis and epithelial-to-mesenchymal transition [29][30][31]43]. Therefore, these data suggest that Mbnl1/2 counteract the function of miR-294 in these processes.…”
Section: Mbnl1/2 Counteracts the Function Of Mir-294 By Binding And Usupporting
confidence: 58%
See 1 more Smart Citation
“…Consistent with cellular phenotypes, RT-qPCR analysis verified that mesenchymal marker Cdh2 and key transcription factors promoting epithelialto-mesenchymal transition (EMT) are upregulated in Mbnl1/2 overexpressing ESCs (Fig 6E). We and others have previously shown that miR-294 promotes ESC proliferation and G1/S transition, and inhibits apoptosis and epithelial-to-mesenchymal transition [29][30][31]43]. Therefore, these data suggest that Mbnl1/2 counteract the function of miR-294 in these processes.…”
Section: Mbnl1/2 Counteracts the Function Of Mir-294 By Binding And Usupporting
confidence: 58%
“…Furthermore, we tested whether Mbnl1/2 can promote the expression of their targets through 3′UTR. We previously constructed luciferase reporters bearing 3′UTR of Vim, Rhoc, Tgfbr2, Cdkn1a, and Lats2 . Luciferase assay showed that MBNL proteins promoted the activity of luciferase reporters bearing 3′UTR of Tgfbr2, Cdkn1a, and Lats2 (Fig C and D).…”
Section: Resultsmentioning
confidence: 95%
“…67, 68 Because of this unique mechanism, PAC-1 is increasingly being used as a tool to directly activate procaspase-3 in a variety of biological settings. 66, 67, 69, 70 In addition, PAC-1 and derivatives have shown synergy with experimental therapeutics 18, 48 and with the anticancer drug paclitaxel. 55 …”
Section: Introductionmentioning
confidence: 99%
“…This depletion of the labile zinc pool restores procaspase-3 enzymatic activity, allowing for cleavage of procaspase-3 to caspase-3 and the initiation of the execution pathway of apoptosis. [42] PAC-1 is now widely used as a tool compound for the induction of apoptosis [51, 59, 67, 68, 82, 83], and for the direct activation of procaspase-3 downstream of the mitochondria. [8487] In addition, multiple independent studies have confirmed the direct procaspase-3 activation mechanism, [48, 85, 88] for example in detailed studies with selective caspase inhibitors, [85] selective caspase substrates, [48] and in Bax/Bak double knockout cells.…”
Section: Pac-1mentioning
confidence: 99%